PERBANDINGAN PENENTUAN KADAR TIROKSIN ENZYME LINKED IMMUNOFLUORESCENT ASSAY (ELFA) DAN ENZYME LINKED IMMUNOSORBANT ASSAY (ELISA) - Faizah Yunianti; Siswanto Darmadi; M Y. Probohoesodo; Budiono Budiono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
The determination of thyroxin (T4) is known as a good indicator to know the condition of thyroid function. In the hyperthyroid state, are shown clearly the increased levels of T4, while in the hypothyroid state their levels always decrease. The T4 levels change due to the physiological and pathological conditions on the ability of thyroxin binding globulin (TBG). The T4 measurement can be performed using an enzyme-linked fluorescent immunoassay (ELFA) or enzyme-linked immunosorbant assay (ELISA). Both ELFA and ELISA can detect T4 antigen. In these research fifty one randomized samples sera from the Clinical Pathology laboratory, at Dr. Soetomo Hospital, consisting of 11 males and 40 females, were studied. They were comparing using ELFA and ELISA to know the levels of T4. In this study the method used is a cross sectional observational, and the statistical analysis with nonparametric Spearman Correlation Rank’s test and Wilcoxon Signed Rank’s Test. In the results by using ELFA were found the mean and SD values 8.78 μg/dL/5.39 μg/dL, whereas by ELISA 11.06 μg/dL/5.38 μg/dL. These results showed a correlation between ELFA and ELISA with rs 0.576. The T4 levels results showed as follows, hypothyroid ELFA 8 (15.7%), ELISA 6 (11.8%); normal levels ELFA 32 (62.7%), ELISA 29 (56.9%); hyperthyroid ELFA 11 (21.6%), ELISA 16 (31.4%) with p 0.090 which was not considered significant. It can be concluded from the showen results that in the determination of T4 concentration using ELFA gave a lower yield compared with ELISA. Further examination is required by special treatment of the sample or other way to find out which one is the best way for determination of T4 levels.